2001
DOI: 10.1074/jbc.m010364200
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Modified Human Malonyl-CoA Decarboxylase Blocks the Glucose-induced Increase in Malonyl-CoA Level but Has No Impact on Insulin Secretion in INS-1-derived (832/13) β-Cells

Abstract: The long-chain acyl-CoA (LC-CoA) model of glucosestimulated insulin secretion (GSIS) holds that secretion is linked to a glucose-induced increase in malonyl-CoA level and accumulation of LC-CoA in the cytosol. We have previously tested the validity of this proposal by overexpressing goose malonyl-CoA decarboxylase (MCD) in INS-1 cells, but these studies have been criticized due to: 1) the small insulin secretion response (2-4؊fold) of the INS-1 cells used; 2) unknown contribution of the ATP-sensitive K ؉ (K AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
5

Year Published

2001
2001
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 26 publications
(47 reference statements)
8
84
5
Order By: Relevance
“…However, LC-CoA also stimulates K ATP channel activity in patch-clamped ␤-cells (44,45), an effect seemingly at odds with a role of LC-CoA as a glucose-derived stimulus/secretion coupling factor. Furthermore, prevention of the glucose-induced rise in malonyl-CoA levels by overexpression of malonyl-CoA decarboxylase has no impact on GSIS (33,46), a finding recently confirmed by the laboratory that developed the malonyl-CoA/LC-CoA hypothesis (47). Similarly, treatment of ␤-cells with Triacsin C, an inhibitor of LC-CoA synthetase, does not impair glucose responsiveness (33,46).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…However, LC-CoA also stimulates K ATP channel activity in patch-clamped ␤-cells (44,45), an effect seemingly at odds with a role of LC-CoA as a glucose-derived stimulus/secretion coupling factor. Furthermore, prevention of the glucose-induced rise in malonyl-CoA levels by overexpression of malonyl-CoA decarboxylase has no impact on GSIS (33,46), a finding recently confirmed by the laboratory that developed the malonyl-CoA/LC-CoA hypothesis (47). Similarly, treatment of ␤-cells with Triacsin C, an inhibitor of LC-CoA synthetase, does not impair glucose responsiveness (33,46).…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, prevention of the glucose-induced rise in malonyl-CoA levels by overexpression of malonyl-CoA decarboxylase has no impact on GSIS (33,46), a finding recently confirmed by the laboratory that developed the malonyl-CoA/LC-CoA hypothesis (47). Similarly, treatment of ␤-cells with Triacsin C, an inhibitor of LC-CoA synthetase, does not impair glucose responsiveness (33,46). In a modification of the original hypothesis, it has recently been suggested that malonyl-CoA/ LC-CoA might be important for the potentiating effect of fatty acids on GSIS, since experiments with triacsin C and malonylCoA decarboxylase overexpression diminished this action of fatty acids in ␤-cell lines and rat islets (47), although different results were obtained by another laboratory with malonyl-CoA decarboxylase (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human C-peptide (synthesized from a human proinsulin cDNA) is packaged in an identical fashion to mouse C-peptide and insulin in granules, but is immunologically distinct from mouse endogenous C-peptide and serves as a reporter from transfected cells. MIN6 cells cotransfected with pcDNA3 control DNA plus human pro- insulin DNA exhibited 160 Ϯ 5.2% (p Ͻ 0.005) of basal human C-peptide secretion in response to glucose, an appropriate increase in human C-peptide secretion in response to glucose in this assay system (55,56). In contrast, overexpression of Munc18c-WT or Munc18c-Y219F reduced glucose-stimulated secretion to 115 and 121% of the basal level, respectively (Fig.…”
Section: Tyr 219 Confers Glucose-induced Phosphorylation To Munc18c-bmentioning
confidence: 96%
“…However, the kinetics of insulin release and of proinsulin biosynthesis, and the metabolic signals mediating these processes, are not identical [3,8]. In fact, the role of various glycolytic and TCA cycle intermediates in glucose-stimulated insulin secretion is controversial [7,[9][10][11][12][13][14][15][16], and even less is known about the metabolic signals for glucose-stimulated insulin production. A previous report by Alarcon et al suggested that succinate is the key signal for glucose stimulation of preproinsulin mRNA translation [3].…”
Section: Introductionmentioning
confidence: 99%